Pengaruh layanan informasi peminatan terhadap kemantapan pilihan sekolah lanjutan - Andi Muhammad Kursi (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
The research is analyzing the effect of the Study Program Selection information services to the students in SMPN 2 Maros? (ii) How is the analysis result of the students choices in the implementation of Study Program Selection information to the consistency of high school choice made by the students of SMPN 2 Maros before and after the services? (iii) Whether or not the service influences the students’ choices in selecting schools? The result of the research shows that (i) the implementation of Study Program Selection information ran effectively and resulted positive responses from the students; (ii) The analysis result of the students consistency of high school choice made by the students before giving the information was averagely low, however the result analysis after giving information was high; (iii) the inferensial statistic analysis result shows the positive effect of the implementation of Study Program Selection information the consistency of high school choice made by the students of SMPN 2 Maros.